Preparing for NATOs Warsaw Summit: The challenges of adapting to strategic change - Trine Flockhart (Danish Institute for International Studies (DIIS), 2015)
This report is about how NATO might adapt to a shifting strategic environment. The strategic environment that is currently unfolding seems likely to be characterized by complexity and increased diversity in both power and principle. The report focuses on how the Alliance needs to respond to the on-going changes by moving forward at the upcoming Warsaw Summit from the decisions taken at the September 2014 summit in Wales. The report starts from the premise that, although the decisions taken in Wales were important and long overdue, they are not sufficient to facilitate NATOs continued adaptation to a fundamentally changed strategic environment. The challenge for NATO in the future will be to find a way to contribute to European and global security in a strategic environment in which the Alliance and "the West" have a diminished role among new and (re)-emerging actors and in which liberal values and Western principles for order-making can no longer be assumed to be universal. The report suggests that NATO should assume the development of a future strategic environment that can best be described as a "multi-order world". NATO should prepare for such a multi-order world by collective defence initiatives from the Wales Summit and by revitalizing NATOs partnership policy. The report suggests that "going back to basics" by concentrating on collective defense would be an inappropriate response, as the new strategic environment requires the Alliance to undertake change in all of its three core tasks if it is to remain relevant in a "multi-order world".
Keywords: 300